PERILAKU ZAKAT ELIT AGAMA KOTA MALANG (Studi tentang Konstruk Elit Agama Kota Malang terhadap Zakat Profesi) - Fakhruddin, Erik Sabti Rahmawati (El-QUDWAH, 2011)
This aim of research is to know how the comprehension of elite religion in Malang City in giving zakat profession. This research method used qualitative research stand on social construction Peter L. Berger theory. The result of this research is all research subjects (Muhammadiyah, Nahdlatul Ulama’, and Majelis Ulama’ Indonesia) stated that the law of  profession zakat is a must. This is based on general lafadz about agriculture zakat command. On determining nisab for zakat profession, all think that zakat profession is being  qiyas by gold zakat and commercial. The only is there are differences of percentage. Muhammadiyah said the percentage of zakat profession is 2.5 %. But Nahdlatul Ulama’ said the percentage of zakat profession start from 2,5%-3,3%. Besides, MUI stated there are two views, they are 2,5 % and 2,5% - 5% for ihtiyath. The time to give zakat could be direct when getting income or collecting in one year.Key words: zakat profession, income, nisab, haul.